Rho/ROCK-dependent inhibition of 3T3-L1 adipogenesis by G-protein-deamidating dermonecrotic toxins: differential regulation of Notch1, Pref1/Dlk1, and β-catenin signaling - Bannai, Yuka; Aminova, Leila R.; Faulkner, Melinda J.; Ho, Mengfei; Wilson, Brenda A. (Frontiers in Cellular and Infection Microbiology, 2012)
The dermonecrotic toxins from Pasteurella multocida (PMT), Bordetella (DNT), Escherichia coli (CNF1-3) and Yersinia (CNFY) modulate their G-protein targets through deamidation and/or transglutamination of an active site Gln residue, which results in activation of the G protein and its cognate downstream signaling pathways. Whereas DNT and the CNFs act on small Rho GTPases, PMT acts on the α subunit of heterotrimeric Gq, Gi and G12/13 proteins. We previously demonstrated that PMT potently blocks adipogenesis and adipocyte differentiation in a calcineurin-independent manner through downregulation of Notch1 and stabilization of β-catenin and Pref1/Dlk1, key proteins in signaling pathways strongly linked to cell fate decisions, including fat and bone development. Here, we report that similar to PMT, DNT and CNF1 completely block adipogenesis and adipocyte differentiation by preventing upregulation of adipocyte markers, PPARγ and C/EBPα, while stabilizing the expression of Pref1/Dlk1 and β-catenin. We show that the Rho/ROCK inhibitor Y-27632 prevented or reversed these toxin-mediated effects, strongly supporting a role for Rho/ROCK signaling in dermonecrotic toxin-mediated inhibition of adipogenesis and adipocyte differentiation. Toxin treatment was also accompanied by downregulation of Notch1 expression, although this inhibition was independent of Rho/ROCK signaling. We further show that PMT-mediated downregulation of Notch1 expression occurs primarily through G12/13 signaling. Our results reveal new details of the pathways involved in dermonecrotic toxin action on adipocyte differentiation, and the role of Rho/ROCK signaling in mediating toxin effects on Wnt/β-catenin and Notch1 signaling, and in particular the role of Gq and G12/13 in mediating PMT effects on Rho/ROCK and Notch1 signaling.